Household food insecurity is independently associated with poor utilization of maternal healthcare services in Bangladesh - Ghose Bishwajit; Sanni Yaya (FACETS, 2017)
Introduction: Food insecurity at the individual level has been shown to be associated with the adoption of risky behavior and poor healthcare-seeking behavior. However, the impact of household food insecurity (HFI) on the utilization of maternal healthcare services (MHS) remains unexplored. In this study, we aimed to investigate whether or not household food insecurity was associated with non/inadequate utilization of MHS.